2002
DOI: 10.1001/archotol.128.7.801
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Submandibular Gland Excision With Parotid Duct Ligation for Treatment of Sialorrhea in Children

Abstract: Bilateral SGE with PDL is a safe and consistently efficient procedure for the treatment of chronic sialorrhea in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 14 publications
0
50
1
3
Order By: Relevance
“…However, our evidence can be interpreted to suggest that more-invasive procedures that aggressively target all 4 major salivary glands are perhaps more effective than less-invasive procedures. The trend Puraviappan et al 52 Glynn and O'Dwyer 48 McAloney et al 46 O'Dwyer and Conlon 35 Puckett et al 32 Fear et al 24 Pogrel 23 Brown et al 22 Bailey and Wadsworth 21 Cranin and Bennett 19 Crysdale 20 Cotton and Richardson 17 Morgan et al 18 Massengill 14 Chait and Kessler 11 Guerin 13 Dundas and Peterson 12 Massengill 14 Glass et al 10 Brody 7 Wilkie and Brody 8 Wilkie 4 Martln and Conley 51 Syeda et al 47 Greensmith et al 45 De et al 42 Shirley et al 43 Stern et al 41 Panarese et al 39 Wilson and Henderson 38 Klem and Mair 36 Mankarious et al 37 Becmeur et al 34 Webb et al 33 Varma et al 31 Burton et al 30 Rosen et al 29 O'Dwyer et al 27 Shott et al 28 Crysdale and White 26 Brundage and Moore 25 Hornibrook 49 Uppal et al 44 Crysdale et al …”
Section: Commentmentioning
confidence: 99%
“…However, our evidence can be interpreted to suggest that more-invasive procedures that aggressively target all 4 major salivary glands are perhaps more effective than less-invasive procedures. The trend Puraviappan et al 52 Glynn and O'Dwyer 48 McAloney et al 46 O'Dwyer and Conlon 35 Puckett et al 32 Fear et al 24 Pogrel 23 Brown et al 22 Bailey and Wadsworth 21 Cranin and Bennett 19 Crysdale 20 Cotton and Richardson 17 Morgan et al 18 Massengill 14 Chait and Kessler 11 Guerin 13 Dundas and Peterson 12 Massengill 14 Glass et al 10 Brody 7 Wilkie and Brody 8 Wilkie 4 Martln and Conley 51 Syeda et al 47 Greensmith et al 45 De et al 42 Shirley et al 43 Stern et al 41 Panarese et al 39 Wilson and Henderson 38 Klem and Mair 36 Mankarious et al 37 Becmeur et al 34 Webb et al 33 Varma et al 31 Burton et al 30 Rosen et al 29 O'Dwyer et al 27 Shott et al 28 Crysdale and White 26 Brundage and Moore 25 Hornibrook 49 Uppal et al 44 Crysdale et al …”
Section: Commentmentioning
confidence: 99%
“…Conversely, sialorrhea occurs in more than 80% of patients with Parkinson's disease or cerebral palsy [5,14,19], and many authors tried to define the correct approach in the treatment of sialorrhea. Intraparotid or submandibular glands injection of botulinum toxins [4,8,13,17], anticholinergic drugs (glycopyrrolate, scopolamine or atropine) [1,5,6,12,19], and surgical procedures (salivary gland excision, salivary duct ligation, salivary duct rerouting) [2,16] are reported as the main therapeutic strategies to this aim. Despite their efficacy in reducing overabundant salivation in noncancer patients, in clinical practice, the use of anticholinergic drugs is limited by their cardiac, neurological, gastrointestinal, and urinary side effects, and botulinum toxins or surgical procedures are considered the most suitable treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva production from minor salivary glands is sufficient to prevent xerostomia. STERN et al [120] reported persistent significant improvement in both quality of life and sialorrhoea at a mean follow-up of 4.2 yrs. Two retrospective studies [119,121] have documented a significant decrease in numbers of hospitalisations and lower respiratory tract infections following the procedure.…”
Section: Treatment For Aspiration Of Salivamentioning
confidence: 97%
“…Another potential treatment for aspiration of oral secretions involves the ligation and/or removal of salivary glands. Bilateral ligation of submandibular and parotid ducts or excision of submandibular glands with parotid duct ligation have been reported in children [119][120][121][122]. Both procedures are effective at reducing sialorrhoea (table 5).…”
Section: Treatment For Aspiration Of Salivamentioning
confidence: 99%